Primary plasma cell leukemia: A report of two cases of a rare and aggressive variant of plasma cell myeloma with the review of literature - Prithal Gangadhar; Zulfikar Ahmed; Muktha R Pai; I Sandhya (Wolters Kluwer Medknow Publications, 2016)
Plasma cell leukemia (PCL) is a rare and aggressive variant of myeloma accounting for 2-3% of all plasma cell dyscrasias characterized by the presence of circulating plasma cells. The diagnosis is based on the % (≥20%) and absolute number (≥2x10 9 /L) of plasma cells in the peripheral blood. The incidence of primary PCL (pPCL) is very rare and reported to occur in <1 in a million. It is classified as either pPCL occurring at diagnosis or as secondary PCL in patients with relapsed/refractory myeloma. pPCL is a distinct clinicopathological entity with different cytogenetic and molecular findings. The clinical course is aggressive with short remissions and survival duration. We report two cases of pPCL, both having acute onset of illness, varied clinical presentation with one of them showing "hairy cell morphology," with rapidly progressing renal failure, and was not suspected to be plasma cell dyscrasia clinically. A detailed hematopathological evaluation clinched the diagnosis in this case. It is recommended that techniques such as immunophenotyping by flow cytometry and protein electrophoresis must be performed for confirmatory diagnosis. A detailed report of two cases and a review of PCL are presented here.